Wireless sensor networks for water quality (pH) monitoring - Lo, Kuan Luen. (2011)
As a result of the recent development in communication technology, there is an increase utilization of wireless sensors due to their lower costs. The vast amount of applications of sensor networks include healthcare, military, agriculture and many more. Through utilization of such sensor networks, it has allowed for cost effective sensing where manual human observation is cost ineffective.